Effect of spore density of arbuscular mycorrhizal fungi on production of yellow passion fruit seedlings - Cavalcante, Uided Maaze Tiburcio; Maia, Leonor Costa; Melo, Aline Maria Magalhães; Santos, Venézio Felipe dos (Pesquisa Agropecuaria Brasileira, 2002)
Species and density of arbuscular mycorrhizal fungi indicated for increasing growth of yellow passion fruit seedlings were investigated in an experiment using a completely randomized design, with factorial arrangement of 5 x 3 + 1, considering five AMF species (Gigaspora albida, Gigaspora margarita, Acaulospora longula, Glomus etunicatum and Scutellospora heterogama), three inoculum densities (200, 300 and 400 spores/plant) and a non-inoculated control with three replicates, in fumigated soil with 3 mg dm-3 of P and pH 5.3. There was no significative interaction between density of inoculum and the AMF species in relation to host growth. However, shoot dry biomass and leaf area reached maximum values in the treatment with 300 spores/plant. Seedlings inoculated with G. albida, G. margarita and G. etunicatum presented higher growth, colonization, and spores density in the rhizosphere than those associated with A. longula and S. heterogama, whose growth was similar to the control. The inoculation of passion fruit with three of the tested AMF promoted plant vigour, and reduced the period of time for transplanting to the field.